Exploration of the effects of gender and mild esophagitis on esophageal pain thresholds in the normal and sensitized state of asymptomatic young volunteers. Issue 9 (3rd July 2013) - Krarup, A. L.; Gunnarsson, J.; Brun, J.; Poulakis, A.; Edebo, A.; Ringström, G.; Drewes, A. M.; Simrén, M.
Abstract Background Clinical data suggest gender differences in gastrointestinal pain, but very little experimental data exist. Esophageal painful thresholds to mechanical, thermal, electric, and chemical stimuli can be measured with the esophageal multimodal pain model. The aim was to measure the effect of gender and mild esophagitis on esophageal pain perception. Methods Thirty‐five healthy asymptomatic volunteers [19 men, median age 29 (22–56 years)] underwent upper GI endoscopy, 24 h pH/impedance measurement, and multimodal esophageal pain stimulation before and after sensitization with acid. Stimulus intensities at painful thresholds were recorded. Key Results Men had higher pain thresholds (PT) to mechanical stimulation (mean volume: men 20.9 ± 10 mL vs women 15.2 ± 6.8 mL, P = 0.02) and more men tolerated the maximum acid challenge (58% vs 20%, P = 0.03). There were no differences between genders for PT to 1 thermal stimulation [mean stimulation time (men, women): heat; 20 ± 5 s vs 21 ± 6 s or cold; 33.3 ± 20.1 s vs 20.7 ± 21.4 s, P > 0.2], 2 electrical current (mean current: men 17.6 ± 9.2 mA vs women 12.9 ± 3.7 mA, P = 0.11), or 3 acid volume [median volume: men 200 (20;200) mL vs women 133 (40;200) mL, P = 0.2]. Fifteen asymptomatic subjects had mild esophagitis (10 men, all Los Angeles A). There were no differences in esophageal PT between subjects with normal endoscopy or mild esophagitis (all P > 0.3). Conclusions & Inferences The effects of gender and mild esophagitis on esophageal multimodal pain perception have been measured in asymptomatic volunteers. The study suggests that gender, not mild esophagitis, tends to influence mechanical and chemical esophageal pain.